Effects of textual input enhancement and written recall on Iranian pre-intermediate EFL learners’ noticing and intake of present perfect tense - Nahavandi, Naemeh (2015)
The present study investigated the effects of textual input enhancement and written recall on the development of the present perfect tense by Iranian pre-intermediate EFL learners. It examined the effects of textual input enhancement (TIE) in isolation and in combination with written recall (WR) on noticing and subsequently on intake of present perfect tense. Intake was further divided into receptive and productive knowledge of present perfect tense. Furthermore, there was an attempt to understand the effect of TE in isolation and in combination with written recall on comprehension of texts. Besides, the relationship between noticing and reconstruction was investigated. To achieve this end, 96 EFL students in pre-intermediate level of proficiency were randomly assigned to a control and two experimental groups. The control group included 31 participants, while the first experimental group (TE) included 34 participants and the second experimental group (TE+WR) included 31 participants. All participants were given six reading texts and comprehension questions to complete. For participants in groups 2 and 3, the input was textually enhanced through bolding, enlargement and underlining. Participants in group 3 were in addition asked to complete a reconstruction task. Noticing in the study was measured through performance on a note taking task, and intake was measured through performance on a grammaticality judgment task and fill-in-the-blank tasks. The results of the Two-Way repeated measure (ANOVA) showed that TE both in isolation and in combination with written recall affected noticing and intake of the present perfect tense significantly. There was a significant difference among pre-test, immediate post-test and the delayed post-test. While the TE group outperformed the TE+WR group in noticing of the present perfect tense, the TE+WR group outperformed the TE group in intake of present perfect tense in both post tests. However, dividing the intake into receptive and productive knowledge, the TE+WR group only outperformed the TE group in productive knowledge of the present perfect tense significantly. Considering reading comprehension, there was no significant effect of TE either in isolation or in combination with written recall on comprehension of texts. Besides, there was a positive significant relationship between noticing and reconstruction. Furthermore, the results of attitude survey questionnaire and semi-structured interview with 11 students (TE=6) & (TE+WR=5) showed that students held positive attitudes toward the employed treatment. The study concluded with a number of theoretical and pedagogical implications.